2016
DOI: 10.1007/s00038-016-0856-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in waterpipe smokers: a meta-analysis

Abstract: ObjectivesTo quantify by meta-analysis the relationship between waterpipe smoking and cancer, including cancer of the head and neck, esophagus, stomach, lung and bladder.MethodsWe performed a systematic literature search to identify relevant studies, scored their quality, used fixed and random-effect models to estimate summary relative risks (SRR), evaluated heterogeneity and publication bias.ResultsWe retrieved information from 28 published reports. Considering only highquality studies, waterpipe smoking was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…However, the vast majority of these examiners did not know that tobacco was in the nargile (15). A study conducted in Egypt indicates that 26% of boys and 5% of girls consumed nargile, and as many as 22% of Israeli children used nargile once a week (16). Some studies have shown that passive smoking may be related to the level of parents' education and socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of these examiners did not know that tobacco was in the nargile (15). A study conducted in Egypt indicates that 26% of boys and 5% of girls consumed nargile, and as many as 22% of Israeli children used nargile once a week (16). Some studies have shown that passive smoking may be related to the level of parents' education and socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…However, the published data on HNSCC risk in relation to cigar and water‐pipe smoking, compared to cigarette smoking, is limited. The published studies are generally based on male populations, small number of exclusive cigar or water‐pipe smokers and insufficient information is given about frequency and duration of smoking, which limits the possibility of proper determination of cancer risk . Moreover, a part of tobacco smokers are so‐called polytobacco users as they use multiple tobacco products the same time or change their habits when smoking .…”
Section: Changes In Pattern Of Smokingmentioning
confidence: 99%
“…The published studies are generally based on male populations, small number of exclusive cigar or water-pipe smokers and insufficient information is given about frequency and duration of smoking, which limits the possibility of proper determination of cancer risk. 18,[21][22][23][24] Moreover, a part of tobacco smokers are so-called polytobacco users as they use multiple tobacco products the same time or change their habits when smoking. 5 If not recognized properly by investigators this group could contribute to unforeseen diffused results of studies.…”
Section: Changes In Pattern Of Smokingmentioning
confidence: 99%
“…World Health Organization and cause gastric cancer directly by epigenetic effect and indirectly through inflammatory response) [5,6] b) Smoking [4] (especially waterpipe tobacco smokingSmoking flavored tobacco through a long pipe attached to a water bowl) [7] c) Blood group A [7] d) Proton pump inhibitor (Cause hypergastrinemia which leads to gastrointestinal neoplasia) [7,8] (7) e) Pernicious anemia [7] f) Organ transplant recipient [7] g) Alcohol (production of prostaglandins, lipid peroxidation and the generation of oxygen radical species leads to gastric cancer) [4] h) Overweight and obesity (BMI > 25) (Obesity is associated with low-grade chronic inflammatory state, with increased production of TNF, IL-6, MCP-1 and C-reactive protein.…”
Section: Risk Factor Of Stomach Cancer A) H Pylori Infection [4] (Clmentioning
confidence: 99%
“…Low socioeconomic status [4] iii. Gastro esophageal reflux [7] Purpose Sa-um (Fermented pork fat) [29] Sour pancakes (Fermented local food in China) [30] Bekang (Fermented soya bean) [30] Soda (Alkali)…”
Section: Risk Factor Of Stomach Cancer A) H Pylori Infection [4] (Clmentioning
confidence: 99%